Stock boundaries for fisheries assessment and management in the Mediterranean: the Balearic Islands as a case study - Antoni Quetglas (Scientia Marina, 2012)
The stock concept plays a pivotal role in fisheries assessment and management. Stocks are defined according to biological, geographical, economic or socio-political factors. The General Fisheries Commission for the Mediterranean (GFCM) has established thirty management geographical sub-areas (GSAs) based on political and statistical considerations rather than biological or economic factors. Here, we present our view on the main biological and ecological aspects that should be considered for delineating different management units in the Mediterranean. We focus on the Balearic Islands (GSA05) as a case study highlighting its specificities compared to the adjacent coast of the Iberian Peninsula (GSA06), but the approach could be generalized to the problem of identifying stock boundaries in other areas. The work is based on published information from different marine disciplines such as geomorphology, ecology and fisheries, combined with the analysis of new data coming from official fishery statistics and scientific surveys. This approach avoids the important drawbacks (inconclusive results, high costs) of other time-consuming techniques used in stock identification, such as genetics. According to the information presented, we conclude that GSA05 should be maintained as an individualized area for assessment and management purposes in the western Mediterranean.